Los juegos electrónicos y su relación con el desarrollo socio-afectivo de los niños y niñas del primer grado de educación general básica de la “unidad educativa fiscomisional San Francisco de Asís’’ de la ciudad de Loja en el periodo 2013-2014”. Lineamientos propositivos - Villalta Ochoa, Tatiana del Carmen (2014)
This thesis is titled:‟‟ THE GAMES ELECTRONIC AND THEIR RELATIONSHIP WITH BASIC GENERAL EDUCATION FIRST GRADE CHILDREN SOCIO- AFFECTIVE DEVELOPMENT THE BASIC GENERAL EDUCATION FIRST GRADE CHILDREN OF „‟ SAN FRANCISCO DE ASIS‟‟ SCHOOL LOJA CITY PERIOD 2013- 2014‟‟,Which was developed according to the academic regulations of the National University of Loja. The General objective was to analyze the relationship of electronic games in the Socio- affective Developing of the Basic General Education First Grade Children of „‟ San Francisco de Asis‟‟ School, Loja city period 2013- 2014. The methods used were: scientist, deductive, inductive, analytic and statistical model. Techniques and instruments which were used were: a parent is survey to determine the use and type of electronic games used by children; and, the Emotional Intelligence Programme applied to children to assess the Socio- affective Development. According the result of parents survey concludes that: 58% of then use electronic games with educational purposes; 23% sports with entertainment purposes; 7% of strategy and struggle with entertainment purposes; and, 5% adventure and recreational purposes. The Emotional Intelligence Program Results are concluded that: 94% of children observed presented positive responses in emotional development program; and, 6% negative responses.